2018
DOI: 10.1021/acsnano.8b04758
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Graphene-Based Materials: Focus on Human Health and the Environment

Abstract: Graphene and its derivatives are heralded as “miracle” materials with manifold applications in different sectors of society from electronics to energy storage to medicine. The increasing exploitation of graphene-based materials (GBMs) necessitates a comprehensive evaluation of the potential impact of these materials on human health and the environment. Here, we discuss synthesis and characterization of GBMs as well as human and environmental hazard assessment of GBMs using in vitro and in vivo model systems wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
423
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 481 publications
(434 citation statements)
references
References 348 publications
7
423
1
3
Order By: Relevance
“…In this context, the question about toxicity and immune compatibility becomes central for future nanomedical applications of graphene‐based materials including GO, which has been addressed in an increasing amount of studies . When injected into the blood stream, or administered through the airway, acute GO exposure at high doses can cause pulmonary inflammation, cardiovascular and systemic toxicity in mice and rats . GO can also adversely affect fecundity; some studies report toxicity to germ cells and reduced fertility in male mice that might depend on elevated cellular reactive oxygen species contents and subsequent DNA damage induction that in turn triggers apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the question about toxicity and immune compatibility becomes central for future nanomedical applications of graphene‐based materials including GO, which has been addressed in an increasing amount of studies . When injected into the blood stream, or administered through the airway, acute GO exposure at high doses can cause pulmonary inflammation, cardiovascular and systemic toxicity in mice and rats . GO can also adversely affect fecundity; some studies report toxicity to germ cells and reduced fertility in male mice that might depend on elevated cellular reactive oxygen species contents and subsequent DNA damage induction that in turn triggers apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…Prior to focus on these biological effects, scientists should carefully characterize the materials [40]. It has been reported that the number of graphene layers, the average lateral size and the carbon-to-oxygen (C/O) atomic ratio play key role in determining the biological effects [13].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Due to these interactions, the safety and toxicity of GBMs have been extensively evaluated in vitro and in vivo in various studies. In a recent review by Fadeel et al, it has been emphasized that these different properties of GBMs govern their biological effects and scientists should not consider graphene as a single material but rather focus on each individual GBM separately in order to better understand the structure-activity relationships [13].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Moreover,i tp rovidest echniques for safe handling and methods for minimizing the toxicityo fn anoscale carriers for in vivo application. [18][19][20][21] These nanoscale carriers can significantly improve the bioavailability of ad rug and decrease the dose of administration, thereby enhancing its therapeutic efficacy with lowers ide effects. The anti-inflammatory activity of NSAIDs can compatibility,b ut size, shape, agglomeration state, and toxicity (presence of contaminants) can cause undesired inflammation.…”
Section: Introductionmentioning
confidence: 99%